2016
DOI: 10.18203/2349-3291.ijcp20164588
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and laboratory profile of dengue fever in children during an outbreak - one year study at tertiary care hospital, Chennai, Tamilnadu, India

Abstract: Background: Dengue fever is a mosquito borne arboviral disease which is of global concern. It is endemic in tropical countries with annual incidence of 7.5 to 32.5 million cases. It commonly affects the young adults and paediatric cases of Dengue haemorrhagic fever has high mortality. The objective of this study was to assess the clinical and laboratory profile and outcomes of dengue fever in children of less than 18 years of age. The study was conducted for a period of one year during an outbreak, in a tertia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 12 publications
4
10
1
Order By: Relevance
“…The present study demonstrates the peak incidence of cases in the months, between August-October in contrast to a study done by Kabilan et al who found more cases in September-January. 9 The predominant age group in our study was between 6-10 years (52.9%) followed in order by 1month 5year (30.4%) and 11<15 years (16.6%) which is contrary with findings of Gurudeep et al who reported 59% of cases in children between 10-15 years but on par with findings of Sharma NL et al 10,11 Male were predominant than female (54.6%) in our study as similar to many studies. In our study 76.4% presented with dengue fever with warning signs, 9.2% without warning signs and 14.4% with severe dengue.…”
Section: Resultscontrasting
confidence: 85%
“…The present study demonstrates the peak incidence of cases in the months, between August-October in contrast to a study done by Kabilan et al who found more cases in September-January. 9 The predominant age group in our study was between 6-10 years (52.9%) followed in order by 1month 5year (30.4%) and 11<15 years (16.6%) which is contrary with findings of Gurudeep et al who reported 59% of cases in children between 10-15 years but on par with findings of Sharma NL et al 10,11 Male were predominant than female (54.6%) in our study as similar to many studies. In our study 76.4% presented with dengue fever with warning signs, 9.2% without warning signs and 14.4% with severe dengue.…”
Section: Resultscontrasting
confidence: 85%
“…A cyclical pattern of increased transmission coinciding with monsoon and post monsoon as it is the breeding season for Aedes mosquitos. Similar finding was also seen in the studies done by Ahmad S et al and Sharma NL et al 8,5 Out of the 360 patients, 32 cases (37%) were from Vallioor and Panagudi which are urban areas. It is worth to note that only 84 cases (23%) from the rural areas which include Vellamadamand Thovalai.…”
Section: Discussionsupporting
confidence: 88%
“…In the study done by Sharma NL et al the ratio was 1.2:1. 5 This may be due to factors like traditional full body covering in females compared to males and males are more exposed to mosquito bites as they play more often in open fields.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, there are studies specifically performed in pediatric age group. Nagaram et al [20] and Sharma et al [21] performed their studies exclusively amongst children and reported the mean age of patients to be less than 10 years. However, workers like Patel et al (2016), [22] similar to present study did not impose any age restriction and reported the age range of patients from 1 to 76 years.…”
Section: Discussionmentioning
confidence: 99%